The Effect of Kahoot! Game in Teaching Reading Comprehension Achievement - Marsa, Shella Septina; Kuspiyah, Hastuti Retno; Agustina, Eka (JET (Journal of English Teaching), 2021)
Kahoot! Game is one of the advancements in learning technology. It can facilitate and motivate the students for being active and understanding the content of the text. This study aimed to find out whether there is or not any significant difference between the students who are taught by using Kahoot! Game and the students who are taught by using conventional game and to find out the impact of using Kahoot!. Altogether in this study, the writer used mixed-method and explanatory sequential mixed method design which involving 39 students of the fourth-semester students of English Education Program of STKIP Nurul Huda by using reading comprehension test for quantitative data and observation, questionnaire, and interview for qualitative data. The findings were the effect of Kahoot! Game in teaching reading comprehension achievement is a very high impact on engagement, perception and motivation, and positive attitude. It influenced students’ reading comprehension achievement. Therefore, it can be concluded that by using Kahoot! Game with high engagement, perception, motivation, and positive attitude of the students can influence their reading comprehension achievement.